Spatio-temporal patterns in the biomass, species composition and nitrogen content of drift macroalgae in an urbanised coastal embayment - Juan Manuel Valero-Rodriguez; Tim Dempster; Wei Wen Wong; John A. Lewis; Perran L. M. Cook; Stephen E. Swearer (Journal of Applied Phycology, 2024)
Understanding spatio-temporal variability in the production of drift macroalgae is useful for monitoring and assessing the influence of local anthropogenic nutrient sources on coastal ecosystems. In this study we: (1) assessed how the drift macroalgal community composition and biomass have changed over a 22-year period in Port Phillip Bay (a large coastal embayment in Victoria, Australia); and (2) measured the amount of accumulated nitrogen in drift macroalgae and the contribution of anthropogenic nitrogen sources through isotopic analysis. The surveys revealed little overlap in species composition (<13%) and a significant decrease in standing stock biomass (from 631 to 49 g m -2 ) between surveys (1995/1996 and 2017/2018). This was associated with a high degree of turnover (β-diversity) at the genus level between surveys (mean – 0.53), resulting in distinct communities at all sites, particularly among red algal genera. In addition, the occurrence of ephemeral macroalgal blooms and a semi-perennial mat of the red macroalga Botryocladia sonderi at 10-15 m depth at locations close to nutrient sources indicate drift macroalgae are important nutrient accumulators in the bay. Isotopic analysis revealed a high contribution of anthropogenic-derived nitrogen (δ 15 N > 17‰ and ~ 3% N content) at depths and locations close to nutrient sources, particularly at times of the year when large wastewater discharges occur. Harvesting of drift macroalgae could be a cost-effective solution for offsetting nitrogen inputs from anthropogenic sources, but it will be important to first investigate whether harvesting results in negative impacts to associated fauna or nutrient cycling.